Legal Analysis of the Reform of the Criminal Procedure Guidelines Based on the Republic of Indonesia Law Number 1 of 2023 Concerning the Criminal Code - Saija, Jovita Agustien; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
The 1945 Constitution of the Republic of Indonesia affirms that Indonesia is a state of law. One of the important principles of a state of law is the existence of an independent judicial power and free from the influence of other powers in administering justice in order to uphold law and justice. The approach method used in this study is the normative legal approach. The normative approach, also known as legal studies, positive legal studies, doctrinal law, and pure law, focuses on written regulations or prevailing community norms. Based on the results of the research and discussion conducted by the Author, the following conclusions are drawn: 1. Law of the Republic of Indonesia Number 1 of 1946 concerning Criminal Law Regulations (Old Criminal Code) and Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code (New Criminal Code) have different types of criminal penalties and purposes of punishment. The independence and freedom of judges in trying and deciding criminal cases can be divided into 2 (two) points, namely the freedom of judges in accepting, assessing, and constructing every evidence presented in the trial to determine the guilt of the Defendant and the freedom of judges in sentencing the Defendant. The presence of sentencing guidelines in the New Criminal Code has reduced the judge's "absolute discretion", especially in terms of sentencing